MEANING SHIFTS IN PASSIVE CLAUSES FOUND IN THE NOVEL HARRY POTTER AND THE DEATHLY HALLOWS - Melyanda Agustin Chairina (Jurnal Bahasa Lingua Scientia, 2019)
This research was a descriptive qualitative research which aimed to analyze  meaning shifts of the translated novel Harry Potter dan Relikui Kematian. This study discusses the shifts of meaning of passive clauses translated from English (source language) to Bahasa Indonesia (target language). The data for this research was collected both from the original novel Harry Potter and the Deathly Hallows and its Indonesian translation Harry Potter dan Relikui Kematian. The data in this research were passive voice or passive clauses which had translation shifts of form and meaning obtained from the novel. The purposive sampling was used in this study. The sample criteria of the study were all passive clauses found in the novel and their translation shifts.